Mechanisms Linking the Gut-Muscle Axis With Muscle Protein Metabolism and Anabolic Resistance: Implications for Older Adults at Risk of Sarcopenia - Prokopidis, Konstantinos; Chambers, Edward; Ni Lochlainn, Mary; Witard, Oliver C. (Frontiers in Physiology, 2021)
Aging is associated with a decline in skeletal muscle mass and function — termed sarcopenia — as mediated, in part, by muscle anabolic resistance. This metabolic phenomenon describes the impaired response of muscle protein synthesis to the provision of dietary amino acids and practice of resistance-based exercise. Recent observations highlight the gut-muscle axis as a physiological target for combatting anabolic resistance and reducing risk of sarcopenia. Experimental studies, primarily conducted in animal models of aging, suggest a mechanistic link between the gut microbiota and muscle atrophy, mediated via the modulation of systemic amino acid availability and low-grade inflammation that are both physiological factors known to underpin anabolic resistance. Moreover, in vivo and in vitro studies demonstrate the action of specific gut bacteria (Lactobacillus and Bifidobacterium) to increase systemic amino acid availability and elicit an anti-inflammatory response in the intestinal lumen. Prospective lifestyle approaches that target the gut-muscle axis have recently been examined in the context of mitigating sarcopenia risk. These approaches include increasing dietary fibre intake that promotes the growth and development of gut bacteria, thus enhancing the production of short-chain fatty acids (SCFA) (acetate, propionate, and butyrate). Prebiotic/probiotic/symbiotic supplementation also generates SCFA and may mitigate low-grade inflammation in older adults via modulation of the gut microbiota. Preliminary evidence also highlights the role of exercise in increasing the production of SCFA. Accordingly, lifestyle approaches that combine diets rich in fibre and probiotic supplementation with exercise training may serve to produce SCFA and increase microbial diversity, and thus may target the gut-muscle axis in mitigating anabolic resistance in older adults. Future mechanistic studies are warranted to establish the direct physiological action of distinct gut microbiota phenotypes on amino acid utilization and the postprandial stimulation of muscle protein synthesis in older adults.